Oncogenic Brain Metazoan Parasite Infection. (18th September 2013) - Spurgeon, Angela N.; Cress, Marshall C.; Gabor, Oroszi; Ding, Qing-Qing; Tanaka, Tomoko; Miller, Douglas C.
Abstract : Multiple observations suggest that certain parasitic infections can be oncogenic. Among these, neurocysticercosis is associated with increased risk for gliomas and hematologic malignancies. We report the case of a 71-year-old woman with colocalization of a metazoan parasite, possibly cysticercosis, and a WHO grade IV neuroepithelial tumor with exclusively neuronal differentiation by immunohistochemical stains (immunopositive for synaptophysin, neurofilament protein, and Neu-N and not for GFAP, vimentin, or S100). The colocalization and temporal relationship of these two entities suggest a causal relationship.